Functional brain networks in epilepsy: recent advances in noninvasive mapping. Issue 4 (August 2015) - Pittau, Francesca; Vulliemoz, Serge
Abstract : Purpose of review: Epilepsy is one of the most frequent chronic neurological disorders. Recent evidences strongly suggest that epilepsy is due to a dysfunction within an epileptic network, rather than due to the pathological activity of single sources. The aim of this article is to review the recent advances on functional connectivity revealed by noninvasive neuroimaging techniques. Recent findings: Functional connectivity detected through hemodynamic [functional MRI (fMRI)] and electro-magnetic techniques (EEG/MEG) in patients with epilepsy gives an insight into the physiopathogenesis of epileptic network underlying focal epilepsies and specific epileptic syndromes. An increasing number of studies suggest a relevance for surgical cases, both for localizing the focus and for predicting postsurgical cognitive impairment, based on the interactions between pathological and physiological networks. Summary: fMRI and EEG/MEG functional connectivity are complementary techniques and help in identifying the interactions between epileptic activity and physiological networks at different scales. Neuropsychological and neuropsychiatric impairment can be explained by such interactions. fMRI and EEG/MEG functional connectivity help in localizing important drivers of epileptic activity and can also help in predicting postsurgical outcome. Given the large number of methods applied, strict validation, mostly obtained in surgical series, is of utmost importance to understand the benefits and limitations of each technique.